Association of interleukin-18 promoter polymorphism with comorbid conditions of cardiovascular disease - Shams Tabrez; Nasimudeen R. Jabir; Torki A. Zughaibi; Mohd Suhail (Journal of King Saud University: Science, 2023)
Objectives: Cardiovascular disease (CVD) is one of the most clinically relevant pathologies that remains the largest single contributor to global mortality. It is often associated with more than one comorbid condition, which obscures its clinical outcome. The current study aimed to evaluate the possible association of interleukin-18 (IL-18) promoter polymorphism with comorbid conditions of CVD. Methods: We used case-control comparison of specific genotypes of three clinically relevant IL-18 polymorphism hotspots, viz. −656 T/G (rs1946519), −607C/A (rs1946518), and −137 G/C (rs187238) with commonly associated comorbid conditions of CVD such as diabetes, hypertension, and dyslipidemia. For this study, whole blood of CVD patients and healthy control subjects were collected in a citrate coated/plain tube. The routine biochemical parameters were estimated in each sample, and DNA samples were extracted for PCR amplification for further sequencing of targeted amplicons using Sanger method. Results: The studied biochemical parameters showed a significant increase in CVD patients compared with control individuals. Fasting glucose and glycosylated hemoglobin (HBA1C) showed an increase from 4.82 to 8.6 (p < 0.05) and 4.33 to 8.2 (p < 0.05), respectively. The results showed a statistically significant association with CVD-diabetes and CVD-hypertension group with GG, GC, and CC genotype at IL-18 gene locus, rs187238. On the other hand, the CVD-dyslipidemia group showed a positive association with allele distribution at the same hotspot. In addition, the GG, GT, and TT genotype and G and T allele distribution at rs1946519 locus showed statistically significant association with CVD-diabetes, CVD-hypertension, and CVD-dyslipidemia p compared with control subjects. We also observed a statistically significant association of dyslipidemia with three genotypic combinations viz. (rs1946518 AA, rs1946519 GG, rs187238 GG); (rs1946518 AA, rs1946519 GT, rs187238 GG), and (rs1946518 AA, rs1946519 TT, rs187238 GG). Conclusions: Based on our study, we conclude that IL-18 loci, rs1946519 has a significant association with each studied comorbid condition and can be considered a prognostic marker of CVD and comorbidities. Our results are anticipated to be utilized to launch a significant pharmaco-genomic investigation that could identify patients with comorbidities who are more likely to develop CVD.